Maternal Ferritin Levels during Pregnancy and ADHD Symptoms in 4-Year-Old Children: Results from the INMA–INfancia y Medio Ambiente (Environment and Childhood) Prospective Birth Cohort Study - Santa-Marina, Loreto; Lertxundi, Nerea; Andiarena, Ainara; Irizar, Amaia; Sunyer, Jordi; Molinuevo, Amaia; Llop, Sabrina; Julvez, Jordi; Beneito, Andrea; Ibarluzea, Jesús; Imaz, Liher; Ferrin, Maite (International journal of environmental research and public health, 2020)
Ferritin status during prenatal brain development may influence the risk of attention deficit and hyperactivity disorder (ADHD) symptoms in childhood. We investigated the association of maternal ferritin in pregnancy and ADHD-like symptoms in offspring. A total of 1095 mother-child pairs from three birth cohorts of the INMA Project (Spain) were studied. Maternal plasma ferritin in pregnancy was measured at 11.57 weeks of gestation. Children′s ADHD-like symptoms at ages 4–5 years were assessed using the ADHD Rating Scale-IV. The count model of the zero-inflated Poisson regression model showed a significant inverse association between ferritin (continuous variable) and inattention, β = −0.19 (−0.32, −0.07), for boys. Comparing ferritin level by tertile, significant differences were observed between the first tertile (1.98, 20.92) and the second (20.92, 38.79) and third (38.79, 216.5) (μg/L) tertiles. The number of symptoms was lower for those in the third tertile, β = −0.3 (−0.55, −0.5), and for those in the second one, β = −0.37 (−0.6, −0.14). The model stratification by sex also showed this inverse association for boys only, β = −0.21 (−0.34, −0.08). No associations were found between ferritin level and hyperactivity or total ADHD symptoms. High ferritin levels during pregnancy show a protective association with child inattentive-type ADHD symptoms.